The poetry of translation from Chaucer & Petrarch to Homer & Logue - Reynolds, Matthew (Oxford Oxford University Press, 2011)
This is a wide-ranging book which launches a new theory of poetry translation and pursues it through readings of poem-translations from across the history of English literature. It engages with the key debates in translation studies, and offers new interpretations of major works.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Poetry -- Translating; Poetry -- History and criticism